Simbol Alam dalam Antologi Puisi Makrifat Daun-Daun Makrifat Karya Kuntowojoyo: Kajian Semiotika Charles Sanders Pierce - Manurung, Bunga Junita Neti Natalia (Kajian Linguistik dan Sastra, 2024)
Semiotics is a science that studies signs. In Semiotics there are types of signs, one of which is in the form of symbols. Symbols are divided into 3 types. The study aims to explain the types of natural symbols in the poetry anthology Makrifar Daun- Daun Makrifat by Kuntowijoyo. This study is a qualitative study that uses a qualitative descriptive approach. The data in this study are in the form of words, phrases, clauses, and sentences that state the type of symbol. The data source in this study is the poetry anthology Makrifat Daun-Daun Makrifat by Kuntowijoyo. The data collection technique used is the documentation technique and analyzed with three flows including data reduction, data presentation, and drawing conclusions. The results of this study found 54 symbols in the poem which are divided into 8 natural symbols in the form of animals, 6 natural symbols in the form of plants, 22 natural symbols in the form of natural events, and 18 natural symbols in the form of natural objects. Each type of symbol has its own meaning that explains the purpose of the type of symbol. Natural symbols in the form of animals in the poem are found in the words a pair of doves, a dog, a cat, a butterfly, Natural symbols in the form of plants are found in the sentences grass, fragrance, twigs, roses, spruce chips. a sprig of roses, natural symbols in the form of natural events are found in the words full moon, light, universe, rain, dusk then natural symbols in the form of natural objects are found in the words clouds, moon, sun, sky, hills, stars. This study concludes that the natural symbols contained in the poetry anthology Makrifat Daun-Daun Makrifat by Kuntowijoyo not only depict the beauty of nature but also have deep meanings that reflect the spiritual relationship of humans with God and the universe. Understanding these symbols provides new insights into the study of Indonesian literature, especially in revealing the depth of meaning contained in literary works based on symbolism.  Abstrak Semiotika merupakan ilmu yang mempelajari tentang tanda. Dalam Semiotika terdapat jenis tanda yang salah satunya beberbentuk simbol. Simbol terbagi menjasi 3 jenis, Penelitian tersebut bertujuan untuk menjelaskan jenis-jenis simbol alam dalam antologi puisi Makrifar Daun- Daun Makrifat karya Kuntowijoyo.Penelitian ini merupakan penelitian kualitatif yang menggunakan pendekatan deskriptif kualitatif. Data dalam penelitian ini berupa kata, frasa, klausa, dan kalimat yang menyatakan jenis simbol. Sumber data dalam penelitian ini adalah antologi puisi Makrifat Daun-Daun Makrifat karya Kuntowijoyo. Teknik pengumpulan data yang digunakan adalah teknik dokumentasi dan dianalisis dengan tiga alur diantaranya reduksi data, penyajian data, dan penarikan kesimpulan.Hasil penelitian ini ditemukannya 54 simbol dalam puisi tersebut yang terbagi menjadi 8 simbol alam berupa hewan,, 6 simbol alam berupa tumbuhan, ,22 simbol alam berupa kejadian alam, dan 18 simbol alam berupa benda alam. Masing-masing jenis simbol tersebut terdapat maknanya yang menjelaskan maksud dari jenis simbol tersebut. Simbol alam berupa hewan dalam puisi tersebut ditemukan dalam kata sepasang merpati, sekor anjing, kucing, kupu-kupu, Simbol alam berupa tumbuhan ditemukan dalam kalimat rumput, wangian, ranting, mawar, krisik cemara. setangkai mawar, simbol alam berupa kejadian alam ditemukan dalam kata purnama, cahaya, semesta, hujan, senja kemudian simbol alam berupa benda alam ditemukan dalam kata awan, bulan, matahari, langit, bukit-bukit, bintang. Penelitian ini menyimpulkan bahwa simbol-simbol alam yang terdapat dalam antologi puisi Makrifat Daun-Daun Makrifat karya Kuntowijoyo tidak hanya menggambarkan keindahan alam tetapi juga memiliki makna mendalam yang mencerminkan hubungan spiritual manusia dengan Tuhan dan semesta. Pemahaman terhadap simbol-simbol ini memberikan wawasan baru dalam kajian sastra Indonesia, khususnya dalam mengungkap kedalaman makna yang terkandung dalam karya sastra berbasis simbolisme.